Development of Digital Pocket Book Based on Realistic Mathematics Education (RME) Fort Supports Students' Literacy Ability - Rohati Rohati; Marlina Marlina; Sri Winarni; Ade Kumalasari (Jurnal Pendidikan: Teori, Penelitian, dan Pengembangan, 2023)
This research aims to create a digital pocket book that supports reading skills and is based on Realistic Mathematics Education. Research and development are the term for this type of study. This development study was carried out with the use of a 4-D model. A total of 30 students from SMP Negeri 7 Muaro Jambi participated in field trials. The digital pocketbook met the validity, practicality, and effectiveness requirements, according to the findings. Teachers should be able to develop creative ideas for developing teaching materials that support reading skills based on the findings of this study.